IMPACT OF GREEN PARTS POWDER OF LOCALLY CULTIVATED CARROT (DAUCUS CAROTA L.) ON QUALITATIVE AND SENSORY PROPERTIES OF BISCUITS AND CAKE - N. S. Mahdi,; K. A. Shakir, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The current study aimed to identify the effect of adding different concentrations (0%, 1%, 2%, 3%, and 4%) of carrot green parts powder (CGP) into biscuit and cake mixes on final products qualitative and sensory characteristics. The chemical analysis showed that the protein, ash, and fiber contents for wheat flour and for CGP were (10.64%, 0.88%, and 0.48%) and (16.4%, 19.4%, and 18.65%) respectively.  While for the final products the percentages of protein and ash ranged from (10.36% -12.80% protein, 1.03%-1.53% ash) for cake treatments and (13.00 % -20.00% protein, 0.92%-1.43%ash) for biscuits treatments respectively. There was no significant variation among the width averages of biscuit treatments. The highest value for both spread ratio and spread factor were seen in treatments with 2 and 3% added powder. The sensory evaluation analysis indicated that there were no notable differences among the treatments in terms of external characteristics (the nature of surface and crust color). Although the internal characteristics were significantly affected by CGP concentrations, the overall scores for acceptance of the final product showed no significant differences among treatments. Regarding the cake samples, there were no significant differences in external characteristics among the treatments, except the color of the crust for treatment with 2% CGP and the crumb texture (porosity) and the overall acceptance in treatments with 1 and 2%of CGP which showed, significant differences.